The US organic industry: important trends and emerging issues for the USDA - Thilmany, Dawn, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2006)
This publication provides a small glimpse of current trends, emerging issues and potential roles of the public sector in the organic agriculture sector.
April 2006.
Originally published under series title: Agribusiness marketing report.
Keywords: Organic farming -- United States